Producer knowledge and application of mineral supplementation in sheep farming systems - Helbus, Alaina M.; Clemens, Morgan S.; Yankocy, Samantha R.; Stenhouse, Claire (Frontiers in Veterinary Science, 2025)
IntroductionMinerals are critical for ruminant health, reproduction, and productivity, yet deficiencies in grazing systems are common worldwide. This study characterized mineral supplementation practices among Pennsylvania sheep producers and evaluated their knowledge, perceptions, and diagnostic approaches.MethodsAn anonymous Qualtrics survey, conducted from March to August 2024, yielded 168 valid responses from sheep producers statewide.ResultsMost respondents managed small flocks (<20 ewes) and rated minerals as “very important” for both health (77.8%) and reproduction (78%). The majority (91.0%) provided supplemental minerals to their animals at certain or all stages of production. Commercial mineral mixes (72.0%) and salt/mineral blocks (29.8%) were the most frequently used delivery methods, with decisions primarily guided by producer experience, extension recommendations, and peer advice. Interestingly, only 30.7% of respondents had tested their soil/forage and only 9.0% had tested animals for mineral deficiencies, despite recognizing the importance of minerals for health and productivity. Reported health concerns included diarrhea, teeth grinding, and milk fever, while key reproductive challenges were mastitis, weak lambs, and stillbirths. Cost constraints, perceived adequacy of pasture, and flock size were cited as reasons for not supplementing.DiscussionThese findings highlight strong awareness of mineral importance but limited adoption of diagnostic testing, suggesting potential gaps in targeted supplementation that may be more economical.